Modern approach to training of pediatricians - Elena N. Grinko (Педиатрическая фармакология)
Pediatric education should take into account development of intellectual abilities that are necessary for the future specialist. Specifically, they are creativity, critical thinking, an integrated approach to problem solving, emotional intelligence, social and communication skills. These qualities are formed using active and interactive teaching methods.